PENINGKATAN KINERJA DOSEN BERBASIS MODAL SOSIAL DAN DUKUNGAN ORGANISASIONAL DI PTS KOTA SEMARANG - Fauzan Mohammad (Jurnal Bisnis dan Ekonomi, 2012)
The main problems of this research are how social capital which is supported by transformational leadership and clan culturetype gives influence to the lecturers’ performance. The research sample were lecturers of ten private universities in Semarang.The technique of sample drawing was multi stage cluster random sampling. The size of sample by using was Slovin formula.Data were collected by the using questionnaire. The number of the data which able to analize were 275 respondents. Thetechnique of data analysis was moderator quasi model based on the interaction regression. This research result severalfindings (1) structural dimension of social capital gives positive and significant influence to task performance, (2) relationaldimension of social capital gives negative influence to task performance, (3) transformational leadership style does notmoderates the relation of the social capital structural dimension to task performance, (4) transformational leadership stylemoderates the relation of the social capital relational dimension to task performance, (5) the type of clan culture does notmoderates the relation of the social capital structural dimension to task performance, (6) the type of clan culture does notmoderates the relation of the social capital relational dimension to task performance.Key words: performance model, social capital, leadership support..